The Transformation of Public Space in the Shadow of Informality: a Spatial Analysis of GOR Sudiang, Makassar - Andi Andini Nurul Annisa; Nur Natasya; Ibrahim Arifin; Andi Syafirah Nurlayli Amal (Citra Media Publishing, 2026)
The expansion of the informal sector in cities of the Global South has reshaped the function of public space through the interaction of economic activities, urban mobility, and environmental dynamics. This study aims to analyze how the presence of street vendors in the GOR Sudiang area of Makassar City transforms public space into a hybrid economic–mobility space and generates impacts on traffic congestion and environmental degradation. The research employs a qualitative approach with a case study design. Data were collected through field observations, in-depth interviews with vendors and space users, and visual documentation. Thematic analysis was conducted to identify patterns of spatial transformation, mobility-constraining practices, and emerging ecological pressures. The findings reveal four main patterns. First, GOR Sudiang has undergone a functional transformation from a sports facility into a hybrid space combining recreational and informal economic activities. Second, the spatial practices of street vendors and unregulated parking contribute to the narrowing of mobility space and the intensification of congestion, particularly during peak hours. Third, the concentration of economic activities without adequate environmental management infrastructure leads to waste accumulation and declining environmental quality. Fourth, weak public space governance reflects the lack of integration among mobility planning, environmental management, and informal-sector regulation. This study argues that congestion and environmental degradation in public spaces cannot be understood merely as technical transportation issues or individual behavioral problems, but rather as consequences of the social production of space shaped by negotiations between livelihood needs and urban governance capacities.